Adopting the LEAN concept to develop the online car booking service process - Suesat, Nuttaya (Thammasat University Hospital Journal Online, 2022)
Background: Permission to use a government vehicle must be made by submitting a request form to the Vehicle Agency and other involved parties. The buildings were scattered and far away from each other. The demand for car services increases with the number of workloads of various departments on a daily basis. The process is repetitive, complex, and difficult to approve. Therefore, developing online service process is needed. Objective: To analyze the process, reduce wasted operating time, shorten service time and modify the workflow. Material and methods: The analysis was performed regarding the value of vehicle agency to provide comprehensive car service to end customer. Then the creation of a smooth workflow without interruption was done by integrating the development of service processes according to the requesting applicant. The applicants book services through the online system and continually perform measurements and process improvements by applying the PDCA technique. Result: The waiting period for car application approval was reduced to 1 day, the total process time was reduced by 49.66% and 100% of messenger service coordinators. Three workflow can be reduced from 10 steps. Conclusion: As a result of the adoption of the LEAN concept, 1. the waiting period for approval was reduced from two days to only one day. To total process time was reduced by half. No messenger service is needed no longer the workflow was reduced from 10 to 7 steps. It is an integrated development with information systems for system preparation and electronic signature.